Expression and Purification of EPHA2 Tyrosine Kinase Domain for Crystallographic and NMR Studies. (9th November 2016) - Gande, Santosh L.; Saxena, Krishna; Sreeramulu, Sridhar; Linhard, Verena; Kudlinzki, Denis; Heinzlmeir, Stephanie; Reichert, Andreas J.; Skerra, Arne; Kuster, Bernhard; Schwalbe, Harald
Abstract: The receptor tyrosine kinase EPHA2 is overexpressed in several cancers (breast, head and neck, non‐small‐cell lung cancer). Small‐molecule‐based inhibition of the EPHA2 kinase domain (KD) is seen as an important strategy for therapeutic intervention. However, obtaining structural information by crystallography or NMR spectroscopy for drug discovery is severely hampered by the lack of pure, homogeneous protein. Here, different fragments of the EPHA2 KD were expressed and purified from both bacterial ( Escherichia coli, BL21(DE3) cells) and insect cells ( Spodoptera frugiperda, Sf9 cells). 1 H, 15 N HSQC was used to determine the proper folding and homogeneity of all the constructs. Protein from E. coli was well‐folded but unstable, and it did not crystallize. However, a construct (D596–G900) produced in Sf9 cells yielded homogenous, well‐folded protein that crystallized readily, thereby resulting in eleven new EPHA2–ligand crystal structures. We have also established a strategy for selective and uniform 15 N‐amino acid labeling of EPHA2 KD in Sf9 cells for investigating dynamics and EPHA2–drug interactions by NMR. Abstract : EPHA2 tyrosine kinase : EPHA2 is overexpressed in several cancers, but structural analysis is hampered by the lack of stable homogeneous protein. An optimized kinase construct was expressed in Sf9 cells to pursue study by NMR and protein crystallography. This work will aid drug discovery and development.